Purification and Characterization of a Novel Metalloproteinase, Acurhagin, from Agkistrodon acutus Venom - Wang, Wen-Jeng; Huang, Tur-Fu (Thrombosis and Haemostasis, 2002)
Acurhagin, a high-molecular mass hemorrhagic metalloproteinase, was purified from the crude venom of Agkistrodon acutus using anionexchange and hydrophobic interaction chromatography. Acurhagin is a monomer with a molecular mass of 51.4 kDa under non-reducing conditions on SDS-PAGE and 48,133 Da by mass spectrometry. Partial amino acid sequence of its metalloproteinase domain is homologous to other high-molecular mass metalloproteinases from snake venoms. It preferentially cleaved Aα. chain of fibrinogen, followed by Bβ chain, while γ chains was minimally affected. Monitored by RP-HPLC, it extensively degraded fibrinogen into various peptide fragments. In aqueous solution, acurhagin autoproteolyzed to a 30 kDa fragment at 37° C. The N-terminal sequence of the 30 kDa fragment of acurhagin showed a high homology to those proteins consisting of disintegrinlike and cysteine-rich domains. Caseinolytic assay showed that the proteinase activity of acurhagin was slightly enhanced by Ca2+ and Mg2+, but completely inhibited by Zn2+. When treated with metal chelators, acurhagin was completely inactivated. Furthermore, acurhagin exerts an inhibitory effect on ADP-induced platelet aggregation of plateletrich plasma in an incubation-time dependent manner. It also impairs collagen- and ristocetin-induced platelet aggregation by cleaving collagen and vWF, respectively.
Keywords: Snake venom metalloproteinase; Agkistrodon acutus, fibrinogenase; autoproteolysis; platelet aggregation